Pharmacotherapeutic strategies for hepatitis B and hepatitis C coinfection. (4th March 2022) - Jacob, Rachael; Danta, Mark
ABSTRACT: Introduction: Hepatitis B (HBV) and Hepatitis C (HCV) infection place a significant burden on the global health system, with chronic carriage leading to cirrhosis and hepatocellular carcinoma. HBV/HCV coinfection can be seen in highly endemic areas and present a heterogenous group given varying virologic profiles. Coinfected patients have a greater risk of advanced liver disease; hence, diagnosis and early antiviral therapy (AVT) should be a priority. Optimal treatment regimens for coinfected patients remain unknown with differing recommendations, particularly relating to the risk of HBV reactivation whilst on AVT for HCV. Areas covered: This article summarizes the available data on HBV/HCV coinfection with regards to epidemiology, virologic interactions, and risk of HBV reactivation. The authors also provide a framework for the assessment and treatment of coinfected patients. Expert opinion: There is a moderate risk of HBV reactivation in hepatitis B surface antigen (HBsAg) positive patients undergoing HCV direct-acting antiviral (DAA) treatment; however, clinically significant events are rare. The risk of HBV reactivation in HBsAg negative patients undergoing HCV DAA treatment is negligible. Thus, prophylactic HBV treatment in both groups is not required. The authors recommend close monitoring with HBV treatment if there is evidence of HBV reactivation or elevated alanine aminotransferase levels.